2018
DOI: 10.4467/24498939ijcm.18.007.8386
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between the Form of Employment and Employee Training and Developing Opportunities in Organizations

Abstract: In modern organizations, the importance of employee training and development is increasingly emphasized because as it allows them to improve their qualifications and develop new competencies and attitudes useful for the organization. On the other hand, the flexible forms of employment, which are less permanent than indefinite period employment contracts, are increasingly used in organizations. The aim of the paper is to present the relationship between the form of employment and employee training and developin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
1
2
0
1
Order By: Relevance
“…In the case of C6, the result may be justified by the fact that people employed on a contract of mandate more often declare performing individual work than teamwork (Huk, 2011). The results only partially confirmed previous findings about the differences between the self-employed and workers with a contract of mandate with regard to professional development (Kot-Radojewska, 2018). Only in the case of contracts of mandate and its impact on the employers' investments in C4 and C6 was there confirmation of the statements, previously published in the literature on the subject, that the low employability of workers in non-standard FoEs is related to employers' investing less in their development (Bernstrøm et al, 2019;Piwowar-Sulej and Ba ˛k-Grabowska, 2021).…”
Section: Main Findings and Their Theoretical Contributionssupporting
confidence: 71%
See 2 more Smart Citations
“…In the case of C6, the result may be justified by the fact that people employed on a contract of mandate more often declare performing individual work than teamwork (Huk, 2011). The results only partially confirmed previous findings about the differences between the self-employed and workers with a contract of mandate with regard to professional development (Kot-Radojewska, 2018). Only in the case of contracts of mandate and its impact on the employers' investments in C4 and C6 was there confirmation of the statements, previously published in the literature on the subject, that the low employability of workers in non-standard FoEs is related to employers' investing less in their development (Bernstrøm et al, 2019;Piwowar-Sulej and Ba ˛k-Grabowska, 2021).…”
Section: Main Findings and Their Theoretical Contributionssupporting
confidence: 71%
“…Qualitative research by Krasiejko (2016) covering workers employed under contracts of mandate has shown that this FoE can lead to precarization, disappointment with working conditions, and worker frustration. In turn, self-employed people, in comparison to those employed under a contract of mandate, show higher self-esteem and declare more often that they feel appreciated in organizations (Kot-Radojewska, 2018).…”
Section: Theoretical Background and Development Of Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…W badaniu przeprowadzonym w Polsce wykazano, że to zatrudnieni na umowy o pracę na czas nieokreślony, w porównaniu z zatrudnionymi w innych formach, najwyżej oceniają m.in. takie aspekty pracy, jak możliwość rozwoju, awansu czy profesjonalnego szkolenia (Kot-Radojewska, 2018). Przyjmując pespektywę długookresową, zauważa się, że zatrudnieni w formach niestabilnych niejako podwójnie tracą: pracodawcy mniej w nich inwestują, obniżając tym samym ich szanse na przyszłe zatrudnienie (Bernstrøm, Drange i Mamelund, 2019).…”
Section: Umowa O Pracę Na Czas Nieokreślony Jako Standardowa Forma Za...unclassified